2014
DOI: 10.1186/1472-6963-14-272
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care professional education via video conference builds confidence to deliver palliative care in rural and remote locations

Abstract: BackgroundPeople living in rural and remote locations are disadvantaged in accessing palliative care. This can be attributed to several factors including the role diversity and the low numbers of patients with specific conditions, as well as the difficulties rural health practitioners have in accessing opportunities for professional education. A program of multidisciplinary palliative care video conferences was presented to health practitioners across part of northern Australia in an effort to address this pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 34 publications
(46 reference statements)
2
61
0
Order By: Relevance
“…28 Other novel interventions that may help overcome barriers include video conferencing, team-based learning, the use of simulation, online case-based modules, reading literature, and self-reflection. [29][30][31][32] The lack of experienced faculty also can be addressed. The End-of-Life Nursing Education Consortium (ELNEC) courses have been successfully used to prepare graduate nursing faculty to provide palliative care.…”
Section: Discussionmentioning
confidence: 99%
“…28 Other novel interventions that may help overcome barriers include video conferencing, team-based learning, the use of simulation, online case-based modules, reading literature, and self-reflection. [29][30][31][32] The lack of experienced faculty also can be addressed. The End-of-Life Nursing Education Consortium (ELNEC) courses have been successfully used to prepare graduate nursing faculty to provide palliative care.…”
Section: Discussionmentioning
confidence: 99%
“…On follow up 73.7% indicated they consistently considered vision when planning treatment; 50% reported often screen for vision now and 15/19 participants now consider environment & vision. However, 63.2% did not use any of the screening assessments covered; 78% reported increase in comfort levels for providing interventions for low vision including increased activity visibility, increased contrast & organisation of work stations.Ray et al2014 [36]AustraliaCross-sectional cohortElectronic survey using self-report Likert scalesTotal 101, AHPs 20Evaluate VCs with experts delivered monthly for 16 monthsRural16 Palliative care (PC) topicsContent usefulness, confidence of palliative care delivery & influence on practiceContent usefulness: significant difference in ratings between AHPs and MDs/students ( p  = 0.018) and nurses ( p  = 0.018); AHPs found content less useful than MDs and nurses. Practice location, years of working and number of clients seen were not significant.…”
Section: Methodsmentioning
confidence: 99%
“…Some had an examination following the intervention [27, 33, 35], or formal assessment of knowledge before and after intervention [28]. Simpler study designs reported on findings from evaluation instruments administered only after delivery of the education [27, 29, 31, 36, 37]. In addition, three studies gathered qualitative data to evaluate learning and the utility of the methods of e-learning [20, 29, 38].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The acute care setting offers many opportunities for education in palliative care, 28 and online and video education programs have proved effective in developing palliative care knowledge and skills. [29][30][31] To encourage greater uptake of palliative care education opportunities, state licensing boards could encourage or even require palliative care education as part of continuing education requirements.…”
Section: Discussionmentioning
confidence: 99%